Livelihood security and resource conservation through integrated farming system - Singh, J P; Gill, M S (Indian Farming, 2015)
The content of the paper emphasized the need of change in farming system practices and demands an integrated farming system approach. This approach not only fulfills the household needs of a family but also helps in keeping the people away from the hazards of residual toxicity of the chemicals being used in agriculture on a large scale and keep the environment safe by way of minimizing the use of chemicals and increased use of organic sources of the nutrients and plant protection. Further, diversified nature of the project provides huge employment opportunity for unemployed rural youths.